Design optimization of the APF DTL in the SSC-linac - 王志军 何源 吴巍 杨雅清 肖陈 (Chinese physics C, 2010)
A linear accelerator as a new injector for the SSC （Separated Sector Cyclotron） of the HIRFL （Heavy Ion Research Facility Lanzhou） is being designed. The DTL （Drift-Tube-Linac） has been designed to accelerate ^238U^34＋ from 0.140 MeV/u to 0.97 MeV/u. To the first accelerating tank which accelerates ^238U^34＋ to 0.54 MeV/u, the approach of Alternating-Phase-Focusing （APF） is applied. The phase array is obtained by coupling optimization software Dakota and beam optics code LINREV. With the hybrid of Multi- objective Genetic Algorithm （MOGA） and a pattern search method, an optimum array of asynchronous phases is determined. The final growth, both transversely and longitudinally, can meet the design requirements. In this paper, the deign optimization of the APF DTL is presented.